Integrating Trap-Neuter-Return Campaigns Into a Social Framework: Developing Long-Term Positive Behavior Change Toward Unowned Cats in Urban Areas - McDonald, Jennifer L.; Farnworth, Mark J.; Clements, Jane (Frontiers in Veterinary Science, 2018)
Cat management is often discussed in terms of population reduction, with trap-neuter-return (TNR) campaigns commonly organized to manage unowned urban cat populations. However, long-term effectiveness is only possible if positive neutering practises are continued by local residents. Here we discuss how implementing TNR within a wider framework of social engagement has the potential to tackle cat overpopulation and instil long-term positive behaviour change towards them. We demonstrate how community engagement pre-TNR can help establish a baseline of the attitudes, knowledge and behaviour concerning cats. Using a case study, we explore whether this information can be linked with positive intended behaviour based on intentions to arrange for neutering of unowned cats. Structural equation modelling indicated that negative attitudes towards cats and reduced knowledge around neutering reduced the likelihood of positive intended behaviour. This result was underpinned by the indirect effects of perceptions of unowned cats and reduced understanding of their needs. Utilising these results alongside an understanding of the values and motivation of the community allows for tailored and targeted education and intervention. In turn, this addresses the underlying knowledge gaps and perceptions regarding cat welfare. This framework can help address the challenge of cat management because it: (1) takes an integrative approach to identifying the motivations of communities to take responsibility for unowned cats; (2) changes the structure of the social environment, encouraging positive neutering practises for unowned cats. In turn this improves the impact and longevity of TNR campaigns whilst promoting positive welfare change for unowned and owned cats; and (3) appreciates that opinions are likely to vary hugely between areas, therefore providing an adaptable community level approach.